Strategi Komunikasi Interpersonal Pelatih dalam Meningkatkan Motivasi Member GYM untuk Mencapai Target Kebugaran: Studi Kualitatif di Fit Hub Manyar Kertoadjo - Firman Agung Prasusanto; Farikha Rachmawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study focuses on the interpersonal communication strategies employed by trainers in motivating gym members to achieve their fitness goals at Fit Hub Manyar Kertoadjo, Surabaya. The background of this research highlights the importance of communication in the fitness industry, where the success of training programs is not only determined by technical aspects but also by the trainer’s ability to build effective interpersonal relationships with members. The objective of this study is to analyze the forms of interpersonal communication messages used by trainers and their influence on members’ motivation in pursuing fitness programs. This research adopts a descriptive qualitative approach, using in-depth interviews and documentation as data collection techniques, involving experienced trainers and active members of Fit Hub Manyar Kertoadjo. The findings indicate that trainers apply both verbal and nonverbal communication strategies tailored to the characteristics of each member, utilize digital media such as WhatsApp and Instagram to maintain communication continuity, and implement the principles of openness, empathy, supportiveness, positivity, and equality. These strategies have proven effective in enhancing motivation, building self-confidence, and strengthening the emotional bond between trainers and members. Therefore, it can be concluded that effective interpersonal communication from trainers plays a significant role in maintaining members’ training consistency, increasing motivation, and accelerating the achievement of fitness goals. This research is expected to serve as a reference for the development of trainers’ communication skills to support the success of fitness programs in Indonesia.